ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI AKADEMIK SISWA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NU BAHRUL ULUM - Pipot Andriyani (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
This research aims to analyze the factors influencing students' academic achievement in the subject of Islamic Religious Education (IRE) At SMP Nu Bahrul Ulum . The factors examined include student learning motivation, parental support, teacher teaching quality, and school environment. The research method used is a mixed methods approach, integrating quantitative and qualitative approaches. Quantitative approach is used to analyze survey data, while qualitative approach is used to gain in-depth insights into students' experiences and perceptions of these factors. The research sample is randomly selected from several representative SMP geographically. Quantitative data is collected through distribution of questionnaires to selected respondents, while qualitative data is collected through in-depth interviews with a number of students. The results of quantitative data analysis indicate a positive relationship between student learning motivation, parental support, teacher teaching quality, and students' academic achievement in IRE. Qualitative findings provide deeper understanding of these factors, highlighting the important role of interest, motivation, understanding of Islamic values, family support, and school environment in influencing students' academic achievement. Comparisons between quantitative and qualitative results show consistency in the findings obtained. Based on the research findings, it is concluded that comprehensive efforts involving teachers, parents, and the school environment are needed to improve students' academic achievement in IRE At SMP Nu Bahrul Ulum . Teachers need to implement innovative and interactive teaching methods, parents need to provide strong support for Islamic education at home, and schools need to create a conducive and supportive learning environment for students. It is hoped that this research will provide valuable contribution in enhancing the quality of learning and academic achievement of students in the subject of IRE At SMP Nu Bahrul Ulum .